PEMERIKSAAN SILANG MIKROSKOPIS SEDIAAN DARAH PADA LIMA PUSKESMAS KABUPATEN OKU SUMATERA SELATAN - Wurisastuti, Tri; Sitorus, Hotnida; Nurmaliani, Rizki; Satriani, Ade Verientic (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2014)
Ogan Komering Ulu (OKU) district South Sumatra Province is one malaria-endemic areas with Annual Parasite Incidence (API) in 2011 was 0.78 ‰ . Malaria treatment was done in the OKU District is based on microscopic examination. Therefore, quality assurance of microscopist is essential for better malaria case management. Quality assurance with crosschecks was done by microscopists who have gotten formal or informal training in 5 endemic health centers OKU Districts. The result of finger blood smears examination which were positive and 10 % of negative slide would be crosscheck by health department of OKU District and vector born deasease research & development unit Baturaja microscopists. The different examination result between health department of OKU District and vector born deasease research & development unit Baturaja microscopists would be checked by National Institute of Health Research & Development microscopist. The results showed that the reliability value among health centers microscopist and Health Department of OKU district or vector born deasease research & development unit Baturaja microscopist was that no body classified in the cataegory of less or bad. But there was still three microscopists who had an error rate values>5.